Implementasi Pendidikan Seksual Berbasis Nilai Islam pada Anak Usia Dini di Tadika Al-Fikh Malaysia - Azzahra Azzahra; Zuliana Zuliana (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2026)
This study aimed to develop an interactive video as a medium for introducing prosocial and antisocial behavior to children aged 5–6 years in Palembang City. The research employed a Research and Development (R&D) method, utilizing the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The research participants involved subject-matter experts, media experts, educators, and children aged 5–6 years. Data were collected through validation questionnaires, practicality questionnaires, and observations, while the data were analyzed descriptively. The findings revealed that the developed interactive video media was categorized as highly valid and highly practical, and it received very positive responses from the children. The media effectively assisted children in recognizing and distinguishing between prosocial and antisocial behavior. The novelty of this study lies in the development of a needs-based interactive video that is participatory and contextual in nature, making it more effective than the passive video media commonly used in learning activities.